Social Media Addiction and its Association with Sleep Quality Among Medical Students in A Medical College In Tamil Nadu, India - Siddharthan A; V Aljin; S Hariharan; VM Anantha Eashwar (Medsci Publications, 2024)
Background: Medical students' social media addiction disrupts and lowers sleep quality, hurting their everyday life and academic performance, stressing the need for effective ways to promote their well-being and achievement. The study aims to estimate the prevalence of social media addiction and to find out the association with sleep quality among medical students in private medical college. Methodology: A cross-sectional study involving 792 MBBS students from a private medical college in Chengalpattu district, Tamil Nadu, utilized the Bergen Social Media Addiction Scale (BSMAS) to assess social media addiction and the Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality. Data were collected through a pre-tested semi-structured questionnaire and analysed using SPSS version 25. Results: The study revealed a 17.7% prevalence of social media addiction among medical students, significantly associated with poor sleep quality, female gender, and morning social media use. Other factors included dependence on social media for updates, more than three hours of daily use, eye discomfort, Snapchat use, compulsion to post at least six photos and subjective sleep quality, sleep latency, duration, disturbances, use of sleeping medication, and Daytime dysfunction. Conclusions: Research demonstrates a significant correlation between social media addiction and poor sleep quality among medical students, highlighting the need for focused interventions and awareness activities to counteract its harmful influence.